High –temperature conduction mechanism of samarium ferrite substituted sodium niobate ceramics - Kumar D.; Bangwal A.S.; Singh S.; Jha P.A.; Singh P. (My University, 2025)
NaNbO3 is a well known piezoelectric perovskite with better electro-mechanical properties used as transducers. The activation energy is observed to vary with respective phase transitions in NaNbO3. In the present work, NaNbO3 is co-substituted with Sm3+ (donor) and Fe3+ (acceptor) with compositions SmxNa1-xFexNb1-xO3 [x = 0.0–0.1 in the steps of 0.025] by solid-state reaction technique to study the transport properties. The samples were synthesized in single phase along with the lattice expansion with the increase in x. The morphology change from grain-growth to recrystallised state is observed with increment in x. The conductivity is observed to decrease up to x = 0.025 with substitution and further, increases with increment in x. In addition, the variable activation energies are observed with x, leading to alteration in exhaustion region. The mechanism of the variable activation energy with the co-substitution of donor and acceptor substituent's is reported here. © 2020 Elsevier B.V.